PENGARUH INSENTIF DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA KARYAWAN QNB (QATAR NATIONAL BANK) INDOMESIA AREA - Wardiana, I Putu Eka; Riana, I Gede; Sudibya, I Gede Adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Term incentive used in this study is the extent to which incentives can motivate members of the organization (employees) to achieve the goals of the organization (company). The purpose of this study was to analyze the significance of the effect of giving incentive and job satisfaction on organizational commitment and work motiva tion . Research was conducted on the employees of QNB Bank Indonesia Area Surabaya. Data collected by a questionnaire distributed to all employees and employee. Data have been collected and analyzed using descriptive analysis and path anal y sis. The results showed that giving incentive and job satisfaction has a positive and significant impact on organizational commitment. The study also found that giving incentive and job satisfaction of employees  QNB Bank Indonesia Area   Surabaya has a significant positive effect on employee work  motivation a t  the   B ank QNB Indonesia Area Surabaya.